Tradycja przedstawiania zmarłych w Cesarstwie Rzymskim od I do III w. n.e. w świetle źródeł literackich oraz wybranych wizerunków z Rzymu i Egiptu - Martyna Marszałek (Studia Antiquitatis et Medii Aevi Incohantis)
(The Tradition of Representing the Deceased in the Roman Empire from the 1st to the 3rd Century CE in Light of Literary Sources and Selected Portraits from Rome and Egypt): This article discusses how the ancient Romans experienced the loss of their loved ones and what customs were associated with commemorating the dead. The aim of the paper is to show the variability in the way the dead were represented in the period from the 1st to the 3rd century CE. This is made possible thanks to analyses of various ancient written sources and several archaeological discoveries, including portraits from the Fayum, mummy masks and death masks.